Evaluation of Histopathological Changes in Control Biopsies Which Taken 48 Sessions after NBUVB Phototherapy for Early-Stage Mycosis Fungoides. (2nd September 2012) - Zemheri, Ebru; Ozkanli, Seyma; Zindanci, Ilkin; Senol, Serkan; Akbulak, Ozge; Turfanda, Elvan; Toprak, Mehtap; Kosemetin, Duygu; Aydin, Abdullah
Abstract : Background. There are not many studies investigating histomorphological changes in 48 sessions in patients with early-stage MF after narrowband UVB (NBUVB) treatment. Our purpose is to evaluate histological features of phototherapy after 48 sessions and determine which parameters are more reliable for controlling skin biopsies. Methods. Biopsies of 32 patients with early stage of MF, who were treated with NBUVB phototherapy, were histologically evaluated before and after the treatments, including epidermotropism, stratum corneum, epidermal thickness, dermal infiltration, papillary dermal fibrosis, vascular alterations, and other dermal changes. We discuss the histomorphological effects of NBUVB phototherapy on skin biopsies by comparing the responders with nonresponders, with before and after the treatment. Results. 9 patients (28%) did not give any response to treatment. Alleviation in epidermotropism, increases in parakeratosis and normal keratosis, perivascular infiltration, and melanophages, decrease in the lichenoid/patchy lichenoid infiltration pattern after the treatment was statistically significant. Comparing by response, normalization of stratum corneum and epidermis, orthohyperkeratosis, decrease in linearly arranged cells, the lichenoid/patchy lichenoid infiltration, the loss of inflammation were statistically significant in responders group. Conclusion. We detected a significant decrease in linearly arranged cells after phototherapy, indicating that it is an "important diagnostic parameter" in evaluation of therapeutic response.